2020
DOI: 10.1182/blood.2019000953
|View full text |Cite
|
Sign up to set email alerts
|

Immunopathology and biology-based treatment of steroid-refractory graft-versus-host disease

Abstract: Acute graft-versus-host disease (GVHD) is one of the major life-threating complications after allogeneic cell transplantation (allo-HCT). Although steroids remain first-line treatment, roughly one half of patients will develop steroid refractory GVHD (SR-GVHD) which portends an extremely poor prognosis. Many agents, which have shown encouraging response rates in early phase I/II trials for prevention and treatment, have been unsuccessful in demonstrating a survival advantage when applied in the setting of SR-G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 173 publications
0
45
0
Order By: Relevance
“…1a ). High serum concentration of Reg3α, ST2 and sTNFR has been associated with SR-Gut-aGVHD in patients 27 . The 4-DEX-treated recipients also showed marked increase in serum Reg3γ, ST2, and sTNFR as compared with non-GVHD or 1-DEX-treated GVHD recipients (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1a ). High serum concentration of Reg3α, ST2 and sTNFR has been associated with SR-Gut-aGVHD in patients 27 . The 4-DEX-treated recipients also showed marked increase in serum Reg3γ, ST2, and sTNFR as compared with non-GVHD or 1-DEX-treated GVHD recipients (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, although positive response with administration of IL-22 was 100% in low-risk Gut-aGVHD patients, it was <50% in high-risk patients 56 . Patients with SR-Gut-aGVHD belongs to high-risk 27 . Consistent with pathogenic role of neutrophils 43 , 44 , we observed that anti-IL-22 treatment markedly reduced neutrophil infiltration in the colon tissues of Gut-aGVHD induced by Tc22 cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conventionally, glucocorticoids are used as the first-line therapy for GI-GvHD. Unfortunately, almost half of the patients do not respond well to glucocorticoids (3)(4)(5). The survival of patients with GI-GvHD treated with standard steroid regimen ranges between 5% and 30% (4-8).…”
Section: Introductionmentioning
confidence: 99%